The Discovery and Geochemical Characteristics of an Eocene Peridotite Xenolith-Bearing Mafic Volcanic Neck in Coastal Southeast China - Li, Chuanshun; Zhao, Xilin; Jiang, Yang; Xing, Guangfu; Yu, Minggang; Duan, Zheng (Frontiers in Earth Science, 2022)
The mantle beneath coastal SE China evolved from enriched to depleted between the Cretaceous and the Neogene, although the precise timing of this change remains unclear. Here, we focus on a newly discovered Eocene mafic volcanic neck that contains peridotite xenoliths in the Fuding area of Fujian Province, and present new whole-rock Ar–Ar data which indicate that flood basalts formed during the Eocene (ages of 38.5 ± 1.2 and 42.3 ± 2 Ma). The basalt, gabbro, and diabase in the Fuding area are geochemically similar to ocean island basalt (OIB) and have SrI values that range from 0.703794 to 0.703911 (average of 0.703865) and Nd(t) values from 3.05 to 4.56 (average of 3.90). These samples yield two-stage Nd model (TDM2) ages of 0.61 to 0.73 Ga (average of 0.67 Ga). These data indicate that all of these units formed from magmas derived from an OIB-type mantle source, with both the gabbro and diabase units recording minor amounts of crustal contamination. Its OIB type geochemical characteristics may be inherited from crustal materials with similar characteristics. Peridotite xenoliths within the Fuding basalts provide evidence of the nature of the Eocene mantle in this area, especially the post late-Mesozoic evolution of the mantle beneath coastal SE China. The mantle beneath coastal SE China evolved from enriched in the Cretaceous to depleted in the Neogene, with this change occurring during the Eocene.